2022
DOI: 10.1039/d1ob02187g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nitriles from aldehydes using ammonium persulfate by means of a nitroxide-catalysed oxidative functionalisation reaction

Abstract: A methodology for the preparation of nitriles from aldehydes by means of an oxidative functionalisation reaction is reported. It employs employs ammonium persulfate as the primary oxidant and the nitrogen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…With ammonium acetate as the nitrogen source, the imine generated through condensation is readily oxidized by 4-NHAc-TEMPO as the catalyst, which operates with the NO/NO 2 redox couple in combination with oxygen . It was further demonstrated that ammonium persulfate is a suitable oxidant that also serves as a nitrogen source for initial imine formation . Silyl imines readily accessed in situ from aldehydes and hexamethyldisilazane can be oxidized with a stoichiometric oxoammonium salt or a catalytic amount of TEMPO using air as the terminal oxidant to give nitriles …”
Section: Oxidation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With ammonium acetate as the nitrogen source, the imine generated through condensation is readily oxidized by 4-NHAc-TEMPO as the catalyst, which operates with the NO/NO 2 redox couple in combination with oxygen . It was further demonstrated that ammonium persulfate is a suitable oxidant that also serves as a nitrogen source for initial imine formation . Silyl imines readily accessed in situ from aldehydes and hexamethyldisilazane can be oxidized with a stoichiometric oxoammonium salt or a catalytic amount of TEMPO using air as the terminal oxidant to give nitriles …”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…759 It was further demonstrated that ammonium persulfate is a suitable oxidant that also serves as a nitrogen source for initial imine formation. 760 Silyl imines readily accessed in situ from aldehydes and hexamethyldisilazane can be oxidized with a stoichiometric oxoammonium salt 761 or a catalytic amount of TEMPO using air as the terminal oxidant to give nitriles. 762 N-Alkyl imines can react through hydrogen abstraction with TEMPO at very high temperature under air to give N-vinyl imines, which can then engage in aza-Diels−Alder cycloadditions with fullerenes.…”
Section: Oxidations Of Aldehydes and Iminesmentioning
confidence: 99%
“…94 Most recently, the method has been further elaborated to use only ammonium persulfate as both the terminal oxidant and the amine source with 2 and pyridine (Scheme 37), and works with a broad range of aryl and heteroaryl substrates. 95 Lewis, Lambert, Fair and co-workers developed a one-pot oxidative imine formation (Scheme 38). 14 In a one pot synthesis, an alcohol was chemoselectively oxidized to the aldehyde in the presence of an amine that, when base was added, Scheme 35 Deracemization of indolines with (S)-trip.…”
Section: Oxidation Of Aminesmentioning
confidence: 99%
“…To optimize reaction conditions for the oxidation of trifluoromethyl alcohols to TFMKs, we decided to use 2,2,2trifluoro-1-phenylethanol (3a) as a model substrate. As a launching point, we chose reaction conditions similar to those employed in our other oxidative transformations; [20][21][22] namely, alcohol substrate (1 mmol), sodium persulfate (5 equiv), ACT (2; 0.3 equiv), and pyridine (5 equiv), in acetonitrile (2 mL). We heated the reaction mixture at 50 °C for 24 h and observed a 62% conversion into the desired TFMK product, 4a (Table 1, entry 1).…”
Section: Paper Synthesismentioning
confidence: 99%
“…We have used a similar approach to perform a variety of oxidative functionalization reactions, including the conversion of aldehydes into amides 17 and nitriles, 18 and conversion of primary alcohols into carboxylic acids. 19 We subsequently found that by some modification of the reaction conditions, aldehydes can be transformed into esters, 20 amides, 21 and nitriles 22 using a catalytic quantity of 2, without the need for tandem photocatalysis. Key to the success of this approach is the use of sodium persulfate as a terminal oxidant, pyridine as a base, and mild heating.…”
mentioning
confidence: 99%